PENGARUH CORPORATE GOVERNANCE, MODEL BISNIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Daniel Ranbon Bungaran M; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the impact of corporate governance, business model and firm characteristic that are proxied using  firm size, firm profitability, firm growth on dividend policy in Indonesia. The independent variable is corporate governance,  firm profitability, firm growth and business model Disclosure while the dependent variable is dividend policy and firm size is used as a control variable in this study. The data that was used in this research was secondary data from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 and selected by using purposive sampling method. A linear-multiple regression analysis was used to test the hypothesis of this study.               The results showed that corporate governance and firm size does not have significant effect to dividend. On the other hand, firm profitability and business model has a positive and significant effect, while firm growth has a negative and significant effect on dividend policy.